The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1063/1.2336424
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bonding in liquid and supercritical 1-octanol and 2-octanol assessed by near and midinfrared spectroscopy

Abstract: The near and midinfrared spectra of 1-octanol (and 2-octanol) have been measured along the liquid-gas coexistence curve from room temperature up to the critical point and in the supercritical domain along the isotherm T=385 degrees C (and T=365 degrees C) above the critical point of both 1-octanol and 2-octanol for pressure ranging from 0.5 up to 15 MPa. The density values of SC 1- and 2-octanol have been estimated by analysing the near infrared (NIR) spectra in the 3nu(a)(CH) region. A quantitative analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 31 publications
3
24
0
1
Order By: Relevance
“…2 shows the spectral changes of the glycerolrich phase occurring with an increase of temperature from 40 to 200 • C at 10.0 MPa as a result of the change in CO 2 concentration in that phase. The peak at 3696 cm −1 , assigned to the combination mode 2 2 + 3 of the CO 2 , decreases with temperature, which results from a decrease of CO 2 concentration in the glycerol-rich phase when temperature increases from 40 to 200 • C. The peak detected at 4740 cm −1 , assigned to the combination of the (OH) + ı(OH) mode of the associated OH of glycerol, presents a shift towards 4865 cm −1 (dashed lines) when temperature increases, which results from a progressive breaking of the hydrogen bond network of glycerol molecules, as previously reported for other alcohols [22]. In fact, glycerol is a highly flexible molecule forming both intra-and inter-molecular hydrogen bonds; molecular dynamics simulations on this molecule have shown that the number of inter-molecular hydrogen bonds decreases when temperature is increased [43,44].…”
Section: Solubility Of Co 2 and Swelling Of Glycerol In The Glycerol-supporting
confidence: 53%
See 1 more Smart Citation
“…2 shows the spectral changes of the glycerolrich phase occurring with an increase of temperature from 40 to 200 • C at 10.0 MPa as a result of the change in CO 2 concentration in that phase. The peak at 3696 cm −1 , assigned to the combination mode 2 2 + 3 of the CO 2 , decreases with temperature, which results from a decrease of CO 2 concentration in the glycerol-rich phase when temperature increases from 40 to 200 • C. The peak detected at 4740 cm −1 , assigned to the combination of the (OH) + ı(OH) mode of the associated OH of glycerol, presents a shift towards 4865 cm −1 (dashed lines) when temperature increases, which results from a progressive breaking of the hydrogen bond network of glycerol molecules, as previously reported for other alcohols [22]. In fact, glycerol is a highly flexible molecule forming both intra-and inter-molecular hydrogen bonds; molecular dynamics simulations on this molecule have shown that the number of inter-molecular hydrogen bonds decreases when temperature is increased [43,44].…”
Section: Solubility Of Co 2 and Swelling Of Glycerol In The Glycerol-supporting
confidence: 53%
“…This method has been previously successfully applied in phase equilibrium studies for the determination of the CO 2 sorption and swelling in liquids [18,19] and in polymers [20,21]. In particular, we would like to stress that molar absorption coefficients of CHstretching vibrational modes and combination bands are expected to exhibit little sensitivity upon temperature and pressure conditions [20,22,23]. For example, Buback et al [24] have shown that the molar absorption coefficient of combination bands of CO 2 were almost independent of the CO 2 density.…”
Section: Introductionmentioning
confidence: 99%
“…By comparing activation enthalpies from viscosity and self-diffusion (by NMR) measurements for octanol and octanoic acid in n-decane, Iwahashi et al [51] identified additional restrictions (due to more extensive hydrogen bonding) in the octanol system, the values being −27 and −18 kJ/mol, respectively, from both techniques. The octanol value compares well with the cooperative hydrogen bond enthalpy of −22 kJ/mol obtained by Palombo et al [52].…”
Section: Methodssupporting
confidence: 88%
“…The assignment made here is in harmony with other (N)IR spectroscopy studies. [51][52][53] As 2E1H contains many CH n groups, the OH overtone region is strongly overlapped with hydrocarbon combination bands. 47,54 Since the contribution of the CH n groups is practically independent of x, we calculated difference spectra, A(λ,x) = A(λ,x) − A(λ,0), by subtracting the spectrum of neat 2E1Br.…”
Section: B Hydrogen Bond Populations Probed By Near-infrared Spectromentioning
confidence: 99%